Activin receptor-like kinase 3: a critical modulator of development and function of mineralized tissues - Ruan, Xianchun; Zhang, Zhaowei; Aili, Munire; Luo, Xiang; Wei, Qiang; Zhang, Demao; Bai, Mingru (Frontiers in Cell and Developmental Biology, 2023)
Mineralized tissues, such as teeth and bones, pose significant challenges for repair due to their hardness, low permeability, and limited blood flow compared to soft tissues.Bone morphogenetic proteins (BMPs) have been identified as playing a crucial role in mineralized tissue formation and repair. However, the application of large amounts of exogenous BMPs may cause side effects such as inflammation. Therefore, it is necessary to identify a more precise molecular target downstream of the ligands.Activin receptor-like kinase 3 (ALK3), a key transmembrane receptor, serves as a vital gateway for the transmission of BMP signals, triggering cellular responses. Recent research has yielded new insights into the regulatory roles of ALK3 in mineralized tissues. Experimental knockout or mutation of ALK3 has been shown to result in skeletal dysmorphisms and failure of tooth formation, eruption, and orthodontic tooth movement. This review summarizes the roles of ALK3 in mineralized tissue regulation and elucidates how ALK3-mediated signaling influences the physiology and pathology of teeth and bones. Additionally, this review provides a reference for recommended basic research and potential future treatment strategies for the repair and regeneration of mineralized tissues.